Efficiency analysis of the technology of roller formation of finely-grained concrete products - Lazarieva, Olena; Belinska, Svitlana; Lavrinev, Pavlo; Rudenko, Natalia (Eastern-European Journal of Enterprise Technologies, 2019)
Efficiency of using the roller forming technology with forced rotation of the working body (roller or sector) was disclosed. The results of development of an advanced technology of roller formation were presented. This technology features absence of slippage and jamming of the working body relative to the surface of the concrete mixture being formed. Slippage and jamming arise because of growth of inertial forces of freely rotating rollers. Advantages of this technology over the vibrational technology were indicated, namely: – the possibility of combining in one unit the processes of spreading, compacting and smoothing the concrete mixture to enable, first of all, development of highly mechanized and automated technological lines, and increase their productivity: – the possibility of efficient compaction of very hard fine concrete mixtures which in turn creates prerequisites for obtaining durable products, reduced cycles of heat treatment and smaller specific quantity of metal in production; – the possibility of using fine concrete mixtures with scarce cement slurry that do not exceed normative values for a concrete with a coarse aggregate; – the possibility of effective improvement of sanitary conditions for the personnel due to absence of vibration and significant noise reduction; – refuse expensive and in some cases scarce coarse aggregates which ensures significant savings. These dependences characterize and demonstrate increase in the level of pressure of working bodies on the surface of the formed product. As a result, the coefficient of mixture compaction increases from 0.983 for free rotation of rollers to 0.998 for forced rotation.